Diet and exercise in NAFLD/NASH: Beyond the obvious. (21st August 2021) - Semmler, Georg; Datz, Christian; Reiberger, Thomas; Trauner, Michael
Abstract: Lifestyle represents the most relevant factor for non‐alcoholic fatty liver disease (NAFLD) as the hepatic manifestation of the metabolic syndrome. Although a tremendous body of clinical and preclinical data on the effectiveness of dietary and lifestyle interventions exist, the complexity of this topic makes firm and evidence‐based clinical recommendations for nutrition and exercise in NAFLD difficult. The aim of this review is to guide readers through the labyrinth of recent scientific findings on diet and exercise in NAFLD and non‐alcoholic steatohepatitis (NASH), summarizing "obvious" findings in a holistic manner and simultaneously highlighting stimulating aspects of clinical and translational research "beyond the obvious". Specifically, the importance of calorie restriction regardless of dietary composition and evidence from low‐carbohydrate diets to target the incidence and severity of NAFLD are discussed. The aspect of ketogenesis—potentially achieved via intermittent calorie restriction—seems to be a central aspect of these diets warranting further investigation. Interactions of diet and exercise with the gut microbiota and the individual genetic background need to be comprehensively understood in order to develop personalized dietary concepts and exercise strategies for patients with NAFLD/NASH.